2023
DOI: 10.21037/atm-22-6390
|View full text |Cite
|
Sign up to set email alerts
|

Dental pulp stem cells induce anti-inflammatory phenotypic transformation of macrophages to enhance osteogenic potential via IL-6/GP130/STAT3 signaling

Abstract: Background Periodontitis is a major oral condition and current treatment outcomes can be unsatisfactory. Macrophages are essential to the regeneration process, so we investigated the influence of human dental pulp stem cells (hDPSCs) on macrophage differentiation and the microenvironment and the underlying mechanism. Methods hDPSCs were isolated from healthy third molars extracted from patients undergoing maxillofacial surgery. The surface antigens CD73, CD45, CD90 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Murine MSCs preconditioned with IFN‐γ and IL‐1β produce higher IL‐6, intensify macrophages to express IL10, and shift to M2b (Philipp et al., 2018). Healthy DPSCs also secret IL‐6 to induce M2 polarization (Liu et al., 2023), and current results showed that 20 μg/mL LPS has a strong effect on prompting DPCs IL‐6 expression. Thus, it is indicated that LPS‐induced DPCs may activate macrophage to M2b through IL‐6 paracrine pathway.…”
Section: Discussionmentioning
confidence: 61%
“…Murine MSCs preconditioned with IFN‐γ and IL‐1β produce higher IL‐6, intensify macrophages to express IL10, and shift to M2b (Philipp et al., 2018). Healthy DPSCs also secret IL‐6 to induce M2 polarization (Liu et al., 2023), and current results showed that 20 μg/mL LPS has a strong effect on prompting DPCs IL‐6 expression. Thus, it is indicated that LPS‐induced DPCs may activate macrophage to M2b through IL‐6 paracrine pathway.…”
Section: Discussionmentioning
confidence: 61%
“…The cells were then fixed with 4% paraformaldehyde and incubated with anti-human-IL-2-APC (MQ1-17H12; eBioscience, San Diego, CA, USA) for 30 min. Flow cytometry was used for detection and analysis [37].…”
Section: Coculture Assaymentioning
confidence: 99%
“…Stem cells isolated from various tissues have different biological characteristics and different osteogenic differentiation (OD) abilities [ 7 ]. Among them, the stem cells derived from bone marrow are the most studied, and the dental pulp stem cells (DPSCs) are also widely studied because of their excellent OD potential and accessibility [ 8 , 9 ]. Several previous studies have shown that under the control of growth factors, transcription factors, and receptor molecules, DPSCs can differentiate into osteoblasts, adipocytes, odontoblasts, and nerve cells [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%